Increased Isolation of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli From Community-Onset Urinary Tract Infection Cases in Uttarakhand, India - Kumar, Nitin; Chatterjee, Kuhu; Deka, Sangeeta; Shankar, Ravi; Kalita, Deepjyoti (Curēus (Palo Alto, CA), 2021)
Management of community-acquired urinary tract infection (CA-UTI) relies heavily on empirical antibiotic therapy. Knowledge of the proportion of drug-resistant isolates especially extended-spectrum beta-lactamase (ESBL)-producing ( ), and various risk factors for acquisition are essential. Outpatient-treated CA-UTI cases were enrolled (continuously for three months), and microbiological analysis of urine sample was performed for significant bacterial growth followed by identification of conventional and matrix-assisted laser desorption/ionization-time of flight (MALDI-ToF) spectrometry method. Subsequent drug resistance and phenotypic ESBL detection were as per guidelines of the Clinical Laboratory Standard Institute (CLSI, USA). Univariate and multivariate analyses (logistic regression) of known and relevant risk factors of ESBL were performed as per standard statistical technique, using the SPSS computer package (IBM Corp., Armonk, NY).  Results: Two hundred and forty-one samples (of 694 samples) yielded significant growth. Sixty-one of 131 (46.6%) isolates were found to be ESBL producers. Non-beta-lactam antibiotic resistance in ESBL producers was high compared to non-ESBL producers (e.g., 88.5% vs 42.3% for quinolone resistance, 80.3% vs 34.3% for gentamicin resistance, etc.). Multivariate analysis (after univariate analysis detected probable factors of a likely ESBL model) indicated significant associations of ESBL-producing with advancing age (>55 years), prior hospitalization in last one year, use of antibiotics in previous six months, and presence of comorbid illness such as diabetes mellitus and chronic lung disease. High proportion of our community-acquired uropathogens are ESBL-producing and likely resistant to important antimicrobial agents such as quinolones, gentamicin, etc. Factors like advancing age, prior hospitalization, and antibiotic use, as well as comorbidities such as diabetes and chronic lung disease, may be strongly associated with ESBL and should be remembered while administering or preparing guidelines for empiric management of CA-UTI subjects.